Deletions in one domain of the Friend virus-encoded membrane glycoprotein overcome host range restrictions for erythroleukemia. - Hoatlin, M E (1995)
Although the Friend virus-encoded membrane glycoprotein (gp55) activates erythropoietin receptors (EpoR) to cause erythroblastosis only in certain inbred strains of mice but not in other species, mutant viruses can overcome aspects of mouse resistance. Thus, mice homozygous for the resistance allele of the Fv-2 gene are unaffected by gp55 but are susceptible to mutant glycoproteins that have partial deletions in their ecotropic domains. These and other results have suggested that proteins coded for by polymorphic Fv-2 alleles might directly or indirectly interact with EpoR and that changes in gp55 can overcome this defense. A new viral mutant with an exceptionally large deletion in its ecotropic domain is now also shown to overcome Fv-2rr resistance. In all cases, the glycoproteins that activate EpoR are processed to cell surfaces as disulfide-bonded dimers. To initiate analysis of nonmurine resistances, we expressed human EpoR and mouse EpoR in the interleukin 3-dependent mouse cell line BaF3 and compared the abilities of Friend virus-encoded glycoproteins to convert these cells to growth factor independence. Human EpoR was activated in these cells by erythropoietin but was resistant to gp55. However, human EpoR was efficiently activated in these cells by the same viral mutants that overcome Fv-2rr resistance in mice. By construction and analysis of human-mouse EpoR chimeras, we obtained evidence that the cytosolic domain of human EpoR contributes to its resistance to gp55 and that this resistance is mediated by accessory cellular factors. Aspects of host resistance in both murine and nonmurine species are targeted specifically against the ecotropic domain of gp55.